Conceptual Framework for Parametrically Measuring the Desirability of Open Educational Resources using D-Index - Abeywardena, Ishan Sudeera; Raviraja, S.; Tham, Choy Yoong (International Review of Research in Open and Distributed Learning, 2012)
Open educational resources (OER) are a global phenomenon that is fast gaining credibility in many academic circles as a possible solution for bridging the knowledge divide. With increased funding and advocacy from governmental and nongovernmental organisations paired with generous philanthropy, many OER repositories, which host a vast array of resources, have mushroomed over the years. As the inkling towards an open approach to education grows, many academics are contributing to these OER repositories, making them expand exponentially in volume. However, despite the volume of available OER, the uptake of the use and reuse of OER still remains slow. One of the major limitations inhibiting the wider adoption of OER is the inability of current search mechanisms to effectively locate OER that are most suitable for use and reuse within a given scenario. This is mainly due to the lack of a parametric measure that could be used by search technologies to autonomously identify desirable resources. As a possible solution to this limitation, this concept paper introduces a parametric measure of desirability of OER named the D-index, which can aid search mechanisms in better identifying resources suitable for use and reuse.